Dengue Virus Infection Alters Inter-Endothelial Junctions and Promotes Endothelial–Mesenchymal-Transition-like Changes in Human Microvascular Endothelial Cells (2023)
ABSTRACT: Dengue virus (DENV) is a pathogenic arbovirus that causes human disease. The most severe stage of the disease (severe dengue) is characterized by vascular leakage, hypovolemic shock, and organ failure. Endothelial dysfunction underlies these phenomena, but the causal mechanisms of endothelial dysfunction are poorly characterized. This study investigated the role of c-ABL kinase in DENV-induced endothelial dysfunction. Silencing c-ABL with artificial miRNA or targeting its catalytic activity with imatinib revealed that c-ABL is required for the early steps of DENV infection. DENV-2 infection and conditioned media from DENV-infected cells increased endothelial expression of c-ABL and CRKII phosphorylation, promoted expression of mesenchymal markers, e.g., vimentin and N-cadherin, and decreased the levels of endothelial-specific proteins, e.g., VE-cadherin and ZO-1. These effects were reverted by silencing or inhibiting c-ABL. As part of the acquisition of a mesenchymal phenotype, DENV infection and treatment with conditioned media from DENVinfected cells increased endothelial cell motility in a c-ABL-dependent manner. In conclusion, DENV infection promotes a c-ABL-dependent endothelial phenotypic change that leads to the loss of intercellular junctions and acquisition of motility.